Two new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China - Li, Guo-Feng; Li, Hong-Wei; Wang, Chun-Mei; Li, Hua-Feng; Ze, Sang-Zi (Zootaxa, 2018)
Two new species of the genus Oxyporus Fabricius, 1775 are described based on specimens collected in Yunnan Province, China, namely Oxyporus (Oxyporus) fentianae sp. nov. from Mojiang County and Oxyporus (Oxyporus) ningerius sp. nov. from Ninger County. The number of Oxyporus species worldwide is thus increased to 130. Color images of the habitus and aedeagi of the two new species are included. A key to the Oxyporus species of Yunnan Province is provided.